Searching for country risk classes : the relevant variables - Rodríguez Castellanos, Arturo (2004)
The purpose of this paper is twofold. To begin with, depending on the variables considered most relevant in the perception of country risk, it seeks to establish whether countries with similar characteristics as regards this kind of risk can be classified into homogeneous groups. Secondly, it aims to determine whether the groups of variables relevant for discriminating between such groups are identical or different. To this end, the paper is based on a sample of six-monthly values for each of the 9 variables used in the country risk rating published by Euromoney for 149 countries, in the period between September 1992 and September 2002. First, a cluster analysis was made of this sample to identify the groups of countries with homogenous risk characteristics. Discriminant analyses were subsequently applied in a bid to identify the variables with the greatest capacity for distinguishing between such groups